Deep-ELA: Deep Exploratory Landscape Analysis with Self-Supervised Pretrained Transformers for Single- and Multi-Objective Continuous Optimization Problems - Seiler, Moritz; Kerschke, Pascal; Trautmann, Heike (Evolutionary Computation)

Ihre Waffe war der Zeichenstift. Vorstellung der durch den DAB geförderten Arbeit „Die junge Käthe Kollwitz in ihrer künstlerischen Findungsphase" - Schreckenberg, Carolin (Deutscher Akademikerinnenbund e.V.-Newsletter Juni)

Kölner Vorherrschaft über Westfalen? Zu den Ambitionen der Erzbischöfe von Köln (1188–1220) - Schreckenberg, Carolin (775 – Westfalen. Das Buch. Eine Region wird gemacht)

On the impact of various mobility concepts on integrated energy systems - Meschede, Henning; Knorr, Lukas (e-Prime - Advances in Electrical Engineering, Electronics and Energy)

Mit dem Tandem durch die Wende – Aufbau der Benachteiligtenförderung in den neuen Bundesländern - Lippegaus, Petra; Schlegel, Wolfgang; Voigt, Birgit (Geschichten, die die Wende schrieb. Biografien, Erzählungen, Interviews)

Incentive-Based Platoon Formation: Optimizing the Personal Benefit for Drivers - Heinovski, Julian; Ergenç, Doǧanalp; Thommes, Kirsten; Dressler, Falko (IEEE Open Journal of Intelligent Transportation Systems)

Performative Ansätze in der analogen Lehre: Gestaltung von Sprachhandlungsräumen zur Förderung von Lehrkompetenzen im Lehramtsstudium Französisch und Spanisch - del Valle, Victoria (Fremdsprachenlehren und -lernen im Spannungsfeld von digital und analog)

International perspectives and attitudes towards speech and language therapy and multilingualism - Eikerling, Maren; Bloder, Theresa; Castro, Sofía; Rinker, Tanja; Lorusso, Maria Luisa (Clinical Linguistics & Phonetics)

The influence of action outcome probability and expertise on the size of the head-fake effect in basketball - Güldenpenning, Iris; Jackson, Robin C.; Weigelt, Matthias (57. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (ASP))

Die Christen und das deutsche Wesen? Die Ökumenische Bewegung im Dritten Reich - Priesching, Nicole (Una Sancta)

Vorhersagemodell zum ortsaufgelösten Energieeintrag in dichtkämmenden Gleichdrall-Doppelschneckenextrudern - Austermeier, Laura

Die verarbeitungsinduzierte Glasfaserschädigung von Bulk Molding Compounds - Scholle, Maximilian

SoTL und Forschung in den Sozialwissenschaften: Der experimentelle Ansatz in SoTL - Auer, Thorsten Fabian (Scholarship of Teaching and Learning und disziplinäre Forschung: Eine komplexe Beziehung)
Im Rahmen meines SoTL-Projekts habe ich mich aufgrund meiner Vorerfahrungen mit dem experimentellen Forschungsansatz für die Untersuchung der Wirksamkeit von Lernzielen mittels eines Gruppenvergleichs entschieden. In dieser Reflexion stelle ich zunächst heraus, welche Hindernisse und welche Möglichkeiten die Durchführung einer experimentellen Studie im hochschuldidaktischen Kontext mit sich bringt. Anschließend zeige ich anhand konkreter Vorgehensweisen in meinem SoTL-Projekt sowie Bezügen zur experimentellen Wirtschaftsforschung auf, wie wesentliche Punkte für ein fundiertes experimentelles Forschungsdesign in der Hochschullehre umgesetzt werden können und wie Forschende verschiedener Fachrichtungen mit einem derart gestalteten SoTL-Projekt einen Mehrwert sowohl für sich als auch für die Lehrforschung generieren können.

Box-Covariances of Hyperuniform Point Processes - Jalowy, Jonas; Stange, Hanna (arXiv:2506.13661)
In this work, we present a complete characterization of the covariance structure of number statistics in boxes for hyperuniform point processes. Under a standard integrability assumption, the covariance depends solely on the overlap of the faces of the box. Beyond this assumption, a novel interpolating covariance structure emerges. This enables us to identify a limiting Gaussian 'coarse-grained' process, counting the number of points in large boxes as a function of the box position. Depending on the integrability assumption, this process may be continuous or discontinuous, e.g. in d=1 it is given by an increment process of a fractional Brownian motion.

Diagnostisches Handeln im inklusionsorientierten Sachunterricht: Perspektiven aus Wissenschaft und Praxis - Miller, Susanne; Kottmann, Brigitte; Reh, Anne; Schroeder, René (widerstreit sachunterricht)

Investigation failure behavior in the shear tensile test with variety of specimen stiffness - Wolf, Eugen; Brosius, Alexander (MATEC Web of Conferences)
This paper focuses on the failure behavior of clinched specimens with various stiffnesses under shear tensile loading. The primary objective is to assess the influence of the specimen stiffness with an arrangement of clinched joints. The specimen stiffness depends on several variables. In addition to the material selection, the specific choice of geometry and the design of the clinched joints must also be taken into account. A number of experiments was conducted to investigate the failure behavior of specimens with an arrangement of three clinched joints under shear tensile loading. These configurations were subjected to shear tensile tests, with force displacement curves recorded for each specimen to provide a detailed characterization of their structural response. The stiffness is modified by altering the specimen width, which has marginal impact on the maximum force. The experimental findings indicate that reducing the specimen stiffness results in a shift in the type of stress, with the failure behavior becoming increasingly influenced by bending stress. These results offer important insights for the design of clinched joint assemblies, indicating that it is feasible to achieve the desired properties by changing the specimen stiffness.
Keywords: Joining; Sheet Metal; Stiffness; Clinching

Investigation failure behavior in the shear tensile test with respect to the arrangements of clinched joints - Wolf, Eugen; Brosius, Alexander (Materials Research Proceedings)
This paper focuses on the failure behavior of specimens with various configurations of clinched joints under shear tensile loading. The primary objective is to assess the influence of the joining direction and the spatial arrangement of clinched joints on their mechanical performance. A number of experiments was conducted, focusing on three clinched joints arranged in different configurations, each varying in terms of joining direction and spacing. These configurations were subjected to shear tensile tests, with force-displacement curves recorded for each sample to provide a detailed characterization of their structural response. The experimental findings indicate that the specific arrangement of the clinched joints, in terms of joining direction, has a marginal impact on the overall failure behavior. This suggests that intricate modifications to the joining direction are unnecessary to achieve improved mechanical performance in such applications. These results offer valuable insights for the design of clinched joint assemblies, indicating that simplified joining strategies may suffice without compromising structural integrity under shear loading.
Keywords: Joining; Sheet Metal; Clinching

A new joint with versatile properties based on a Reuleaux triangle geometry - Steinfelder, Christian; Acksteiner, Clemens; Brosius, Alexander (CIRP Annals)
Non-rotationally symmetrical joints can have different properties that can be controlled by the joint orientation. This hypothesis is tested using a Reuleaux triangle joint geometry. A tool design is carried out, followed by a numerical sensitivity analysis of the tool geometry. Initial tools were manufactured for experimental investigations and then adapted based on the findings of the sensitivity analysis. The joints are characterized by micrographs, 3D scans, shear tensile tests, head tensile tests and three-point bending tests and compared with a round geometry. The analysis confirms the hypothesis. Thus, joints with adaptable properties can be produced with one tool set.
Keywords: Joining; Forming; Property adjustment

FINN-HPC: Closing the Gap for Energy-Efficient Neural Network Inference on FPGAs in HPC - Jungemann, Linus; Wintermann, Bjarne; Riebler, Heinrich; Plessl, Christian (Proceedings of the 15th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology)